Trust and securities division: customer satisfaction toward public delivery service (PDS) / Siti Amaliya Mohd Radyi (Faculty of Business and Management, 2008)
Improving quality and customer satisfaction have received considerable attention from various parties in recent years. This study examines the exact dimensions contributing in customer satisfaction toward service delivery by Trust and Securities Division (SPAS). BPAS is a part of Account General Department (JANM) as The Registrar in which responsible to manage and admin the Unclaimed Money transaction. This project paper seeks to present objective information concerning the subject of customer satisfaction on the service delivery, as it applies to the current service quality dimension that related to the customer satisfaction. The information from this study will be synthesized to generate a cogent approach to correlate customer service 'with quality and quality service with customer satisfaction. The objectives of this study are to identify the dimension of customer satisfaction towards public delivery service, to determine the relationship between customer satisfaction level and customer demographic factors and also to suggest ways to improve delivery service to satisfy customers toward BPAS. In this study, data was collected regarding the service dimensions and specific items that relate to quality service and satisfaction. Here the researcher was examining methods of identifying customer satisfaction, measuring and using the results to improve the quality of services. For the purpose of the study, the descriptive research was deployed in order to obtain the objectives. Self-administered questionnaire was used as the survey instrument beside interviews as the source of primary data. The technique of questionnaire being used is Likert rating scale. The questionnaires were divided into three sections that need to indicate by respondents. Mean while, jar the population of this study comprise the customers of JANM. Customers attend to the counter as an element of population and 60 people of population will become as a sampling size jar this study. Based on the over view of finding, researcher makes some recommendation to assist organization improve their delivery service.